THE STRATEGIC ROLE OF EDUCATION SERVICES TO REALIZE GENDER EQUALITY IN INDONESIA - Oksiana Jatiningsih; Natsir B. Kotten; Billy Martasandy (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Research purposes This is a strategic service education to realize gender equality in Indonesia. The method used is qualitative, with a study field. As for the participants in the study, these are two state high school teachers in Surabaya. Research result This education plays a very important role in realizing gender equality in Indonesia, though there is still a challenge in reaching gender equality, such as deep gender stereotypes, choice of major, and experience learning what's not fair for a student woman. To reach gender equality in education, it required effort from the government, society, and individuals. This matter covers the implementation of supportive policies on gender equality, improvement of public awareness about the importance of education for women, as well as active support for providing access to equal education for all individuals.